Characterisation of compound semiconductors grown by molecular beam epitaxy - Zhang, Peng Hua (2009)
In this thesis, molecular beam epitaxy (MBE)growth, the optical and luminescence properties and crystalline quality of Ini.x.yGaxAlyAs layers on InP (100)substrates are studied.